The wartime letters of Leslie and Cecil Frost, 1915-1919 - Frost, Leslie M. (Leslie Miscampbell), 1895-1973 (Life writing series., 2007)
Shows how the young men viewed the war, as well as what they observed both during training and from the trenches in some of the war's bloodiest battles. This title presents correspondence between two brothers and their families.